Installation Of Powerwall As An Independent Electricity Source For The Needs Of The Tunjungan House Of Worship Across Tunjungan Village, Kutai Kartanegara Regency - susilo, rizky; Sarri, Cornelius (Outline Journal of Community Development, 2024)
A striking disparity, when connected to big cities that are already supported by fast internet access. However, there are still areas where access to electricity is still hampered. It is true that building a PLN network for these areas will give rise to many challenges. However, there is actually a more efficient solution to this, namely the Solar Power Plant (PLTS) either communally or individually or SHS (Solar Home System). In the utilization of Communal PLTS, there are two types of systems that can be applied, namely the On-Grid and Off-Grid PLTS systems. The term On-Grid refers to a solar panel system that is connected to the PLN electricity network. Panels that use this system will only generate electricity when there is still electricity in the grid. This is because the electricity generated by it cannot be stored as backup energy. While the use of SHS is prioritized for communities that are far apart from each other. In Kutai Kartanegara Regency, there are still many isolated rural areas. One of the areas that is difficult to reach by the PLN electricity network is Tunjungan Village, Muara Kaman District. In 2021, Tunjungan Induk Village has installed an Off-Grid Communal PLTS, while the Tunjungan Seberang area is still experiencing problems in reaching electricity. To overcome the problems faced by areas that are difficult to reach by the PLN electricity network, the Community Service Team of the Electrical Engineering Department of the Samarinda State Polytechnic carried out community service in Tunjungan Seberang Village, Tunjungan by installing a Powerwall as an Independent Electricity Source for the needs of the Tunjungan Seberang house of worship, Tunjungan Village, Kutai Kartanegara Regency.